Genetic aspects of strabismus - Ferreira, Rosane da Cruz [UNIFESP] (2002)
Purpose: To evaluate the genetic aspects of strabismus. Methods: Ophthalmic and orthoptic evaluations were performed prospectively on 110 strabismic probands and 478 relatives. We used 3 different criteria in the diagnosis of strabismus: primary diagnosis (dx1) defined as any manifest horizontal or vertical deviation, a secondary diagnosis (dx2) including esophoria (>7 prism diopters) or exophoria (>9 prism diopters), and a tertiary diagnosis (dx3) including abnormal fusional amplitudes, accommodative convergence/accommodation (AC/A) ratio, and/or stereopsis; monofixation syndrome; 4 prism diopters base out; and/or abnormal Maddox test responses. Analyses were carried out within mating types. Results: Hypotheses of autosomal dominant or recessive inheritance with no sporadics were rejected. Based on the dx1, 25% of the families had more than one individual affected and there was vertical transmission in 13%; adding dx2 there were 36% of the families with more than one affected and 21% had vertical transmission; and adding dx3, there were 73% with more than one affected and 51% with vertical transmission. Conclusions: There is evidence for a pattern consistent with an autosomal dominant form of strabismus in most families.